Fighting Lone Mothers' Poverty through in-Work Benefits - Methodological Issues and Policy Suggestions - Chiara Pronzato (Center for Economic Studies and ifo Institute (CESifo), 2013)
Lone mothers are overrepresented among poor people in many European countries. In 1998, in Norway, a welfare reform increased the amount of benefits and introduced working requirements. Using a quasi-experimental model, Mogstad and Pronzato (2012) find a positive effect of the reform on lone mothers' labour supply and a small reduction in poverty. Is the best result that policy makers could obtain in terms of poverty reduction? In this paper, I estimate a discrete choice model of earnings and welfare participation decisions, and use the behavioural estimates to derive the policy parameters which would have minimized poverty among lone mothers.
Keywords: I38; J22; C25; 330; lone mothers; in-work benefits; poverty; discrete choice models; comparison of methods